Penerapan Model Treffinger Berbantuan Video Untuk Meningkatkan Hasil Belajar Pada Materi Energi Perubahan Bentuk Pelajaran IPA Di Sekolah Dasar 3 Merembu - Iin Mahlia Fitriana; Edy Herianto; Siti Istiningsih (Kappa Journal, 2024)
This research aims to determine the effect of implementing the video-assisted treffinger model on energy material changing the form of science learning at SDN 3 MEREMBU. From the results of observations of the material, changes in shape are relatively low. To overcome this, a video-assisted Treffinger learning model was applied. The research method used is quantitative, the research design is Pre-Experimental Design type one group pretest-posttest Design. This research was conducted on one experimental class group which was not randomly selected. From this research, it can be seen that there has been an increase in the average, namely from 58.17 (pretest) to 70.33 (posttest). The results of the normality test on energy changes learning outcomes obtained a pretest and posttest significance value of 0.063<0.065 so the data was said to be normally distributed. Meanwhile, the output results of the paired sample T test show a sig value. (2-tailed) of 0.000. Based on the basis of decision making on the paired sample T test if sig. (2-tailed) < 0.05 then H0 is rejected and Ha is accepted. In the data above the sig value. (2-tailed) of 0.000 < 0.05 indicates a better effect. In the interpretation table, the R square coefficient of 0.80-1.000 is included in the very strong category so it can be concluded that the video-assisted Treffinger model has a very strong influence on learning outcomes for class 4 science energy changes material. subjects at SDN 3 Merembu Bengkel for the 2023/2024 academic year